Analysis Of Directive Utterances in “Some by Me” Advertisement In Instagram - Nurjannah Nurjannah (Social Science Research Journal, 2025)
This research aims to analyze the use of directive utterances in the “Some by Me” advertisement published on Instagram. The study focuses on identifying the meaning and functions of directive speech acts employed in the advertisement to influence consumer behavior. Using Semantic and pragmatic approaches, this study adopts a qualitative descriptive method to examine the meaning and pragmatic functions of the directives. The data consist of captions from selected Instagram posts by the official “Some by Me” account. The findings reveal that directive utterances in the advertisement are predominantly in the form of imperatives in direct and indirect speech. Additionally, some directives are expressed indirectly through modal constructions and rhetorical questions to maintain politeness and engage audiences more persuasively. The study concludes that directive utterances are a crucial persuasive strategy in digital marketing, especially in beauty product advertisements, where language is carefully crafted to generate interest, urgency, and action among followers. This research contributes to understanding how linguistic choices in social media advertising reflect pragmatic goals and consumer engagement strategies.